2017
DOI: 10.1051/0004-6361/201730978
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a stellar companion to HD 131399A

Abstract: Context. The giant exoplanets imaged on wide orbits (≥10 au) around young stars challenge the classical theories of planet formation. The presence of perturbing bodies could have played a role in the dynamical evolution of the planets once formed. Aims. We aim to search for close companions to HD 131399, a star around which a giant planet has been discovered, at a projected separation of about 80 au. The star also appears to be a member of a wide (320 au) binary system. Methods. We recorded HARPS high resoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…We observed 89 young A-to M-type stars over 3 years or more with HARPS to search for GP and BD with periods less than 1000 days. This survey allowed to detect close binaries around HD106906 and around HD131399 (Lagrange et al 2016(Lagrange et al , 2017. We constrained the period of HD181321B and confirmed the RV trend in HD186704's RV.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…We observed 89 young A-to M-type stars over 3 years or more with HARPS to search for GP and BD with periods less than 1000 days. This survey allowed to detect close binaries around HD106906 and around HD131399 (Lagrange et al 2016(Lagrange et al , 2017. We constrained the period of HD181321B and confirmed the RV trend in HD186704's RV.…”
Section: Discussionmentioning
confidence: 58%
“…A GP companion was discovered with SPHERE around HD131399A by Wagner et al (2016) but is now identified as a background star with similar proper motion (Nielsen et al 2017a). We detected in this survey the presence of a close stellar companion to HD131399A, with a period of 10 days (0.1 au), and an M sin i of 450 M Jup (Lagrange et al 2017).…”
Section: Hd131399mentioning
confidence: 68%
“…In Wagner et al (2016), we reported the detection of a planetary-mass companion on an ∼80 au orbit within the HD 131399 quadruple system (at the time thought to be a triple: Lagrange et al 2017). Subsequent observations determined that this object is likely to be a high-velocity background star with its own significant proper motion aligned with the system (Nielsen et al 2017).…”
Section: Hd 131399abmentioning
confidence: 93%
“…In addition to HD 106906 and HD 131399, which were already known to be spectroscopic binaries (Lagrange et al 2016(Lagrange et al , 2017, 13 stars present evidence of a companion in their RV time series. When enough data were available, we constrained the orbital elements and the m c sin i of the companions (SB1, BD, GP) using yorbit (Ségransan et al 2011).…”
Section: Detected Companions In the Harps Sco-cen Surveymentioning
confidence: 94%